صور الحيوان في شعر شعراء الاسلاميين - أ .م. د. انتهاء عباس عليوي (Prosiding Konferensi Nasional Bahasa Arab, 2021)
The reason for choosing the topic of the research is that Islamic poetry is still on the world scene and on a large scale, as the research talked about an important impact of Arabic literature and to inform the reader and the recipient about an art of their poetic production, including the use of birds and animals in their poetry, and to shed light on part of it neglected by many researchers Those who paid most of their attention to poetic purposes, so I studied what their poems contained of the elements of animated nature, especially birds and animals, so the research drew a plan for itself that requires dividing the research into two sections and a conclusion. Poetics, as for the conclusion, it is a summary of the most prominent results of the research, and what the researcher reached, and they described it as saying that the poetry contained in this research is a precious wealth that deserves to stand on its material, and to arrive at a correct judgment about Arab Islamic poetry since its beginning to the Umayyad era.Keywords: animal, age Islamic l, poetry.